T47D cells arrested at G2M and Hyperploidy Formation Induced by a Curcumin’s Analogue PGV-1 - Muhammad Da’i; Umar Anggara Jenie; Supardjan AM; Masashi Kawaichi; Edy Meiyanto (Universitas Gadjah Mada, 2007)
its chemical structure than curcumin. As a curcumin analogue, PGV-1 was considered to have anticanceractivities. This research was conducted to study the effect of PGV-1 on the cycle progression of T47D cells. Cytotoxiceffects of PGV-1 on T47D cells were determined using MTT assay, and the the effect on cell cycle progressionwas carried out using flowcytometry. Western blot analysis was used to analyze protein expression correspondingto cell cycle progression. The result showed that at the concentration of 2.5 μM PGV-1 inhibited cell cycleprogression through G2/M arrest and induced of cells hyperploidy formation. The hyperploidy formation inducedby PGV-1 was related to the increase of cdc-2 expression. PGV-1 2.5 μM elevated the level of p21 CIP/KIPthrough p53- independent manner. Apoptosis was also induced by PGV-1 at early phase of treatment indicated byPARP cleavage due to activation of caspase-3/7 after 12 h treatment. The results above suggest that PGV-1 inhibitsthe growth of T47D cells targeted on microtubules.Keywords: PGV-1, G2/M arrest, apoptosis, p21